2011
DOI: 10.1371/journal.pone.0021732
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Domain Selectivity in the Cell-Type Specific PKN-Dependence of Cell Migration

Abstract: The mammalian protein kinase N (PKN) family of Serine/Threonine kinases comprises three isoforms, which are targets for Rho family GTPases. Small GTPases are major regulators of the cellular cytoskeleton, generating interest in the role(s) of specific PKN isoforms in processes such as cell migration and invasion. It has been reported that PKN3 is required for prostate tumour cell invasion but not PKN1 or 2. Here we employ a cell model, the 5637 bladder tumour cell line where PKN2 is relatively highly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 50 publications
4
84
0
Order By: Relevance
“…PK-N3 plays a pivotal role in maintaining cell morphology and cell mobility. 54,55 However, a role for PK-N3 in the activation of the Nrf2 pathway has never been reported. This is first study to reveal that PK-N3 participates in Nrf2 phosphorylation and activation of the Nrf2/HO-1 axis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…PK-N3 plays a pivotal role in maintaining cell morphology and cell mobility. 54,55 However, a role for PK-N3 in the activation of the Nrf2 pathway has never been reported. This is first study to reveal that PK-N3 participates in Nrf2 phosphorylation and activation of the Nrf2/HO-1 axis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…With 70% identity between their catalytic domains and 40% in their N-terminal domains, PRK2 and PRK3 share an even lower degree of sequence identity. Recent work has confirmed that all three PRK isoforms can support Rho-dependent cell migration (6) and may be considered to be targets for the development of anti-cancer drugs.…”
mentioning
confidence: 97%
“…In HeLa cells, PRK2 controls the entry into mitosis and exit from cytokinesis (10). Recently, PRK2 was shown to regulate apical junction formation in human bronchial epithelial cells (11) as well as the migration and invasion of 5637 bladder tumor cells (6). PRK1 and PRK2 were also shown to activate the androgen receptor, which plays an important role in the development of prostate cancer (12,13).…”
mentioning
confidence: 99%
“…In the prostate, an increased expression of TXS and the TPα/TPβ isoforms directly correlate with the tumour Gleason score and pathologic stage (32,33,47), where expression of both TXS and the TP is mainly found in areas of perineural invasion, a recognized mechanism by which PCa cells invade the prostatic capsule and metastasize to other tissues (20,32). Significantly in the context of PCa, through detailed mechanistic studies, we recently discovered that both the TPα and the TPβ isoforms directly interact with and regulate signalling by protein kinase C-related kinase/ protein kinase novel (PRK/PKN) (48), a family of 3 AGC kinases that act immediately downstream of phosphatidylinositol 3′kinases, and are strongly, yet differentially, implicated in several cancers (49)(50)(51) and in B-cell development (52). Indeed, in addition to acting as Rho GTPase effectors, activation of the PRKs (e.g., PRK1) in response to androgen receptor (AR) signalling within the prostate catalyses phosphorylation of histone (H)3 at Thr11 (H3pThr11) which, in turn, serves as a specific epigenetic marker, and gatekeeper, of androgen-induced chromatin remodelling and transcriptional activation (48,(53)(54)(55).…”
Section: The Role Of Thromboxane In Cancermentioning
confidence: 99%